La costa del Reino de Granada en la documentación náutica italiana (siglos XIV-XVI) - González Arévalo, Raúl (En la España Medieval, 2008)
A study of nautical charts, portolan charts, documentation from Italian archives, and Cosmographia Ptolomei to define the use of the term "Spain" and the evolution of its meaning, as well as the names of kingdoms and regions of the Iberian Peninsula. Detailed analysis, toponymy and characteristics of geographical features, ports and anchorages of the coast of the kingdom of Granada during the late Middle Ages.